Number of Risk Factors in Down Syndrome Pregnancies - Hussamy, Deana J.; Herrera, Christina L.; Twickler, Diane M.; Mcintire, Donald D.; Dashe, Jodi S. (American Journal of Perinatology, 2019)
Objective The objective of this study was to evaluate risk factor prevalence in pregnancies with fetal Down syndrome, in an effort to characterize efficacy of population-based screening.Study Design Retrospective review of singleton pregnancies with delivery of live born or stillborn infant with Down syndrome from 2009 through 2015. Risk factor categories included maternal age ≥35 years, abnormal serum screening, identification of ≥1 ultrasound marker at 16 to 22 weeks (nuchal thickness ≥6 mm, echogenic intracardiac focus, echogenic bowel, renal pelvis dilatation, femur length <third percentile), and detection of a major fetal anomaly. Statistical analyses included χ2 test and Mantel–Haenszel χ2 test.Results Down syndrome infants represented 1:428 singleton births. All risk categories were assessed in 125 pregnancies and included abnormal serum screen in 110 (88%), ≥1 ultrasound marker in 66 (53%), and ≥1 anomaly in 41 (34%). The calculated risk was at least 1:270 in 93% of Down syndrome pregnancies. More pregnancies had multiple risk factors than had a single risk factor, 90 (72%) versus 30 (24%), p < 0.001. An abnormal ultrasound marker or anomaly was identified in >50% of fetuses in women <35 years and in >75% of those 35 years and older.Conclusion In a population-based cohort, sensitivity of second-trimester Down syndrome screening was 93%, with multiple risk factors present in nearly three-fourths of cases.
Keywords: Down syndrome; ultrasound markers; serum aneuploidy screening